2013
DOI: 10.1002/hed.23007
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative high‐dose‐rate radiotherapy in the management of locoregionally recurrent head and neck cancer

Abstract: HDR-IORT is well tolerated and associated with encouraging in-field disease control. In-field control is associated with improved survival. Further study is warranted to more fully investigate HDR-IORT in the salvage setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…Scala et al reported that 1-year in-field control for patients with negative margins was 82% compared to 56% in those with a positive margin (9). At least five other studies also showed that positive margins (more so for gross residual than microscopic residual) at the time of IORT significantly predicted for in-field failure when compared to close or clear margins (2, 11, 13, 18, 19).…”
Section: Role Of Iort In Head and Neck Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scala et al reported that 1-year in-field control for patients with negative margins was 82% compared to 56% in those with a positive margin (9). At least five other studies also showed that positive margins (more so for gross residual than microscopic residual) at the time of IORT significantly predicted for in-field failure when compared to close or clear margins (2, 11, 13, 18, 19).…”
Section: Role Of Iort In Head and Neck Tumorsmentioning
confidence: 99%
“…In addition, doses of IORT of more than 15 Gy were shown to be associated with better LC (10, 12). Other prognostic factors for LC and RFS include pre-reirradiation recurrence-free interval of more than 12 months (10), use of adjuvant EBRT (9), absence of nodal extra-capsular extension (10), and tumor size (11). Furthermore, patients with neck metastasis who had no PNI, no LVSI, and no involvement of the carotid artery were reported to have better OS after IORT (12).…”
Section: Role Of Iort In Head and Neck Tumorsmentioning
confidence: 99%
“…Resection status at salvage was the most important factor determining local control [17, 19, 21]. Microscopically residual tumours did better with IORT [23], gross residual disease however did not [20, 23]. Adjuvant EBRT after IORT appears to further improve local control, however the small sample size of these studies precludes any definite conclusions [20, 23].…”
Section: Clinical Results With Iortmentioning
confidence: 99%
“…Microscopically residual tumours did better with IORT [23], gross residual disease however did not [20, 23]. Adjuvant EBRT after IORT appears to further improve local control, however the small sample size of these studies precludes any definite conclusions [20, 23]. Wound complications, osteoradionecrosis (ORN), fistulae, and neuropathy are the most common complications [1722] after IOERT; however, these are rare with doses less than 20 Gy [22] and no different than that of re-irradiation with EBRT [16].…”
Section: Clinical Results With Iortmentioning
confidence: 99%
“…The third reason is that with better imaging, we can detect more local and regional recurrences when they are smaller and more amenable to either surgery or radiotherapy (RT). Finally, intensity modulated radiation therapy (IMRT), volumetric modulated arc therapy (VMAT), stereotactic body radiosurgery (SBRS), tomotherapy, improved brachytherapy and protons technology allow us to deliver rRT with increased precision and hence, better patient tolerability [6,7].…”
mentioning
confidence: 99%